Flight Attendants' Digital Communication Strategies Through Self-Disclosure on TikTok: A Phenomenological Study - Dacosta, Kornelia Johana; Putro, Harjono Padmono; Rusmandani, Bachtiar (Institut Komunikasi dan Bisnis LSPR, 2025)
This study explores how flight attendants from Sriwijaya Air Group use TikTok for self-disclosure. It aims to understand theirmotivations, the type of content shared, and its impact on social interactions, self-image, and the airline's public perception. Using a qualitative descriptive method with a phenomenological approach, this research involved five purposively selected informants. The data were analyzed using Joseph DeVito's self-disclosure theory and the Johari Window model. The findings reveal that self-disclosure is performed selectively and strategically. Flight attendants tend to share positive and professional content that aligns with work ethics, such as cabin activities or lighthearted moments in uniform. This practice functions more as a personal branding and impression management strategy rather than intimate emotional disclosure. TikTok serves as a digital stage for shaping a controlled professionalidentity, bridging the gap with the public while indirectly reinforcing the airline's humanistic image. In conclusion, self-disclosure among flight attendants is not a spontaneous act but a calculated communication to balance self-expression with the responsibility of institutional representation.